2017
DOI: 10.1021/acs.jpcc.6b11290
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Methanol Oxidation on Strained Pt Films

Abstract: We report a systematic investigation into the effect of strain on the electrocatalytic activity of films of Pt. We use an electroless deposition process to deposit the Pt onto sputtered Au substrates and characterize their structural and electrochemical properties. We found a direct correlation between the rate of methanol oxidation and the fractional surface coverage of methanol on the compressively strained catalyst surfaces. The fractional methanol surface coverage, Θ M , varied on the Pt surfaces with valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…Lattice straining affects the overall catalytic performance in platinum. [21,26,27] Strasser et al [21] discuss the effect of lattice strain on the activity of core-shell platinum catalysts for ORR, where the Pt-Cu nanoparticles are dealloyed partially to form nanoparticles with a platinum shell and a Pt-Cu core. A moderate reduction in lattice constant, namely, lattice contraction of the platinum is important to enhance the ORR activity of the platinum, although an excessive compressive lattice strain (approximately below −2.5%) deteriorates the ORR activity.…”
Section: Resultsmentioning
confidence: 99%
“…Lattice straining affects the overall catalytic performance in platinum. [21,26,27] Strasser et al [21] discuss the effect of lattice strain on the activity of core-shell platinum catalysts for ORR, where the Pt-Cu nanoparticles are dealloyed partially to form nanoparticles with a platinum shell and a Pt-Cu core. A moderate reduction in lattice constant, namely, lattice contraction of the platinum is important to enhance the ORR activity of the platinum, although an excessive compressive lattice strain (approximately below −2.5%) deteriorates the ORR activity.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of platinum, which has been examined intensively in previous studies, lattice straining affects the overall catalytic performance for ORR in platinum; [32][33][34] lattice contraction is favorable for efficient ORR catalysis on platinum. [32] However, it has been reported that both lattice contraction [35][36][37] and expansion [27] in palladium catalysts enhances the overall catalytic performance for ORR.…”
Section: Discussionmentioning
confidence: 99%
“…It requires an in-depth structural characterization of heterogeneous catalysts, representing a material with a rather complex morphology, as they are composed of oxide-supported metal nanoparticles. The metal nanoparticle shape is directly related to the catalytic behavior since it defines the possible adsorption sites, characterized by different local geometry, and therefore the absorption energy. Another important quantity is the nanoparticle’s internal strain field, since it alters the adsorption probability and, thus, the activity and selectivity of the adsorption sites. Because only a fraction of strained surface atoms can alter the catalytic activity, the atomic site-specific strain determination plays an important role…”
Section: Introductionmentioning
confidence: 99%